Wali Pitu, Bali Province as Tourism Innovation for the Indonesian Halal Tourism Destinations - KHAIRUDIN, Khairuddin (Journal of Environmental Management and Tourism; Vol 13 No 4 (2022): JEMT, Volume XIII, Issue 4(60), Summer 2022DO - 10.14505/jemt.v13.4(60).17, 2022)
This research paper discusses Bali as a halal tourist destination, which is contradictory as a “City of Guardians” amid the brand of Bali as a Hindu City in Indonesia. This article is strongly based on the findings of “Wali Pitu” (seven sainthood) on the island of Bali, in particular that it has not been widely promoted as a halal tourist destination by the local government. The iconic Bali as a Hindu City currently has a double image as a “Wali City” because Wali Pitu tombs were found which differ from those of Wali Songo. Wali Pitu is unique because of its existence at the heart of Hindu civilization in Bali and through a unique process from the cult of Wali Songo. As a new site, Wali Pitu is a new prospect for halal tourism, where several important aspects can invite many pilgrims. Wali Pitu is considered a new halal tourism opportunity to build an image of Muslim holiness amid the hegemony of Hindu society in Indonesia, which serves as the creation of modern religious moderation.